The need for intellectual capital disclosure / Musliha Musman and Dr Salwa Muda - Musman, Musliha; Muda, Salwa (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Recent global economic changes have ushered in a new economic era and had a significant impact on how businesses are managed, and competitive strategies are implemented. The business management changed their basic principles of strategy by emphasising the value of knowledge assets, also known as intellectual capital, which are a type of intangible asset (Konno & Schillaci, 2021). Knowledge assets refer to intellectual resources such as human resources, competence, research and development, customer-based creation, organizational development, and relationships which are more significant in creating a corporate value (Garcia-Perez et al.,2020). Traditional reporting systems have become obsolete because of the knowledge-based economy's revolution. Traditional accounting systems typically produce reports based on financial or quantitative accounting that are focused on material resources, which can be expressed in monetary or quantitative terms. Hence, it measures only the value of the financial and physical assets and offers little information on intangible resources (Dana et al., 2021) such as knowledge or employees' competence which cannot be expressed in monetary or any volume, length, weight measures. Consequently, it lacks an adequate accounting mechanism for measuring and reporting intellectual capital assets to external stakeholders and this results in an information gap between the managers and stakeholders (Garcia-Perez et al.,2020; Mouritsen et al., 2004) and it does not provide the relevant information for the managers or investors to understand how their resources which are in the form of intangibles can create values in the future.